Catalyst for change : Chinese business in Asia - Menkhoff, Thomas; Evers, Hans-Dieter; Chay, Yue Wah; Hoon, Chang-Yau (New Jersey : World Scientific, 2014)
'This book serves as a textbook for courses on Asian studies with a focus on ethnic Chinese entrepreneurs and business management in Asia. It gives a comprehensive Asian perspective on the organizational peculiarities and changing business practices of ethnic Chinese businesses and their leaders who continue to form the backbone of Asia's dynamic economies. The book features selected chapters written by reputable scholars on Chinese business, covering diverse and yet closely related topics such as the role of ethnic identity, trust, guanxi, Chineseness, leadership, change management, learning and knowledge management in organizations owned and managed by ethnic Chinese'--
Includes bibliographical references and index.
Keywords: Chinese diaspora -- Economic aspects; Corporations, Chinese -- Asia; Chinese -- Asia -- Economic conditions; Entrepreneurship -- China; Entrepreneurship -- Asia; China -- Commerce -- Asia; Asia -- Commerce -- China